(untitled) (Journal of Biomedical Investigation, 2010)
Background Yam and plantain of several varieties are staple foods in many parts of the world especially in west and central Africa, parts of Central America and the Caribbean, the Pacific Island and Southeast Asia’ Nutrients such as carbohydrate (starch), protein, minerals and vitamins are derived from them. Since these nutrients are needed for proper functioning of the body and maintenance of good health, yet certain disease conditions like diabetes mellitus need certain dietary restrictions and modifications as a very essential aspect of their management, determination of the nutritional contents of the different varieties of these staple foods is undoubtedly necessary. Objective To determine the value of the different nutrients, present in each of the different species of yam and plantain. This would aid nutritional planning dietary modification in health and diseases like diabetes mellitus. Method The edible portions of the respective five varieties of plantain and yam were carefully mashed and analysed using known analytical methods for each given nutrient. Various percentages were determined using SPSS version 11.0. Results The research focused on the determination of starch, protein and calcium contents of the various varieties of yam and plantain. On a general note, yams had lower starch contents but higher protein and calcium contents than plantains. Dioscorea cayenensis (Yellow yam; ji-ayabe) had the least starch content (9.05%), good Protein (5.60%) and the highest Calcium content (18.04 mg/ 100g). French horn plantain had the highest starch content (34.07%), good calcium (12.02mg/100g) but the lowest protein (3.50%) contents. Discorea dumentorum (Trifoliate yam; ana) had the highest protein content (11.5%), moderate starch (13.3%) and good calcium (14.03 mg/100g) contents. Conclusion Yams are generally more nutritious than Plantains. The observations are important for nutritional planning in health and disease. Increase in production of highly nutritive varieties will lead to improvement in the economic/commercial benefits of the crops.